Project health in scene: Story of experience - Pereira Coelho, Marta; Figueiredo da Silva, Ana Carolina; Nunes Moraes Partelli, Adriana; Coqueiro Secchin, Carla Milena; Pires de Amorim, Emanuelle (Guará Journal, 2025)
It’s crucial to develop programs that educate the public, not only to diagnose problems but also to prevent them through information. To this end, this outreach project, through a play, addresses oral hygiene and the necessary care to prevent parasitic infections in children, in addition to raising awareness about domestic accidents in childhood through posters and conversations. The play, open to improvisation, targeted 1,059 children enrolled in 13 Early Childhood Education Centers in the municipality of São Mateus, Espírito Santo, using creative techniques capable of improving their quality of life.